Reply to letter having reference number BUCG-ABC JV/BRACU/07/18 dated 17th March, 2018 - Brac University (Brac University, 2023)
This record consists of general correspondence regarding reply to letter having reference number BUCG-ABC JV/BRACU/07/18 dated 17th March, 2018 of BRAC University new campus project.